GAMBARAN PENGETAHUAN IBU HAMIL TENTANG PERSALINAN DI DALAM AIR ATAU WATER BIRTH DI PRAKTEK BIDAN HJ. HENDRAYATNI PERIODE APRIL - JUNI TAHUN 2013 - MARDIANI PURBA (LP2MTBM MAKARIOZ, 2021)
The purpose of the study was to describe the knowledge of pregnant women about childbirth in water or water birth in thePractice of Midwife Hj. Hendratni Period April–June 2013 based on age, education, occupation, parity and sources ofinformation. The research is descriptive with a cross sectional approach. The sample was taken by accidental samplingtechnique, the research instrument used a questionnaire sheet with a sample of 30 people, data processing in the form ofediting, coding, scoring, tabulating. The results showed that based on knowledge the majority had less knowledge as manyas 16 respondents (53.4%), based on the age of the majority with less knowledge at the age of 20-35 years as many as 9respondents (30%), based on education the majority had less knowledge in high school education as many as 13respondents ( 43,4%), based on occupation the majority of respondents lack knowledge of work as IRT as many as 14respondents (46.7%), based on parity the majority have less knowledge on multigravida parity as many as 8 respondents(26.8%), based on information sources the majority have less knowledge than sources of non-health personnel informationas many as 10 respondents (33.4%). The conclusion is that the knowledge of pregnant women about childbirth in water orwater birth is lacking. Expected to pregnant women to seek more information about water birth and it is recommended tohealth workers to always provide explanations and counseling and information to pregnant women about water birth.